A thin transferable blue light-emitting diode by electrochemical lift-off - Yaonan Hou (Nano Express, 2020)
We demonstrate a transferable blue light-emitting diode (LED) fabricated using a cost-effective approach. By means of solution-based electrochemical etching, an ultrathin free-standing membrane can be obtained from a commercial III-nitride LED wafer. The membrane, containing a full LED structure (including p-/n-type layers and multiple quantum wells) epitaxially grown on a sapphire substrate, is transferable to foreign substrates with a simple lift-off process facilitated by electrochemical etching. After fabrication, optical properties of the thin film are massively improved, accompanied by a 17-fold enhanced photoluminescence normal to the film surface. Prototype transferable blue LEDs are realized on both a copper-coated glass substrate and a polypropylene substrate. The devices exhibit a high performance with bright emission at 447 nm under electrical injection at room temperature.